Ta’li’mul Insya’ Fie Qismi Ta’liimil LughatilA‘arabiyyati Bi Jami’atil Islamiyyatil Hukumiyyati Langsa Bainal Musykilati Wa Hululiha - abd, RAHMATUN N; Alfi, Khuzaimah; Astuti, Fuji (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
Insya' is the process of writing ideas and opinions and transferring knowledge, information, and experience in good language, good structure, and beautiful language style. The purpose of this study is to find out the problems faced by Arabic Language Education Study Program students in learning inches (composing), as well as to find out what social skills are given by lecturers to solve the problems they face. The method used in this research is the descriptive analysis method, and the instruments used are observation and interviews. The results of the study show that the problems faced by students in learning Insya' are that students experience difficulties in writing what comes to their mind in a language that complies with the rules of grammar, lack of vocabulary, lack their ability to translate into correct Arabic, limited supervision from lecturers and they do not have an adequate environment to support them in writing and it is difficult to develop their opinions due to lack of reading. The solution to this problem is that students need to increase their insight, both inside and outside the classroom, by reading or forming a language environment such as language groups, and lecturers must pay attention to grammar because grammar is an important element in teaching language skills. , and students must familiarize themselves with language practice because with practice students can improve their ability to master vocabulary so that it is easier to master linguistic skills, especially in production skills, namely speaking and writing skills.